PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN PADA KELOMPOK BUDIDAYA IKAN HIAS CANGGU - Nur Aziz, Muhammad Irfan (Universitas Nusantara PGRI Kediri, 2022)
This study aims to examine the variables between work discipline, motivation and compensation for employee inventories in the Canggu ornamental fish farming group. The approach used is quantitative causality, data collection using questionnaires using measuring tools distributed through online forms to respondents. The sample used for this test is IHC employees as many as 40 people. By using reliability test, multiple linear regression analysis, classical assumption and validity test, as well as hypothesis testing using simultaneous F test and partial t test, using the SPSS 23 program tool. The results of this study partially state that compensation with a sig value of 0.724 and work discipline with a sig value of 0.060 no relevant effect or sig. on employee productivity, while partially motivation with a sig of 0.003 has a significant effect on employee productivity. Simultaneously compensation, work discipline and motivation have a significant effect on employee products with a sig value of 0.000.